2019
DOI: 10.1021/acsami.9b10013
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of an Interpenetrating Network of a Poly(ampholyte) and a Cholesteric Polymer and Investigation of Its Hydrochromic Properties

Abstract: A new water-responsive photonic coating based on a hygroscopic amphoteric poly­(ampholyte) has been developed. The material consists of an interpenetrating network between the poly­(ampholyte) and a cholesteric liquid crystalline polymer that reflects light. Swelling of this hybrid material upon contact with water causes a red-shift of the reflection band. As both cation and anion are incorporated in the ionic network, this coating possesses a high stability of its water responsiveness after prolonged and/or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…[29,30] Electrically responsive CLC devices change color and/or transparency under the influence of an electric field and are favorable for tunable light reflectors or privacy windows in which multiple optical modes can be altered dependent on the users' preferences. [31][32][33][34] Other CLC devices responsive to water, [35,36] chemicals, [37,38] mechanical forces, [39,40] and interfacing biomolecules [41,42] demonstrated dynamic photonic properties and could be used as sensors and lasers, for instance. In particular, "smart" temperature-responsive CLCs [43] have found their way into numerous applications as they can alter their pitch length, and thus their reflective color, autonomously with a change in temperature.…”
Section: Scope Of the Articlementioning
confidence: 99%
“…[29,30] Electrically responsive CLC devices change color and/or transparency under the influence of an electric field and are favorable for tunable light reflectors or privacy windows in which multiple optical modes can be altered dependent on the users' preferences. [31][32][33][34] Other CLC devices responsive to water, [35,36] chemicals, [37,38] mechanical forces, [39,40] and interfacing biomolecules [41,42] demonstrated dynamic photonic properties and could be used as sensors and lasers, for instance. In particular, "smart" temperature-responsive CLCs [43] have found their way into numerous applications as they can alter their pitch length, and thus their reflective color, autonomously with a change in temperature.…”
Section: Scope Of the Articlementioning
confidence: 99%
“…Multifunctional skins with structural colors of some organisms, such as the chameleon and the mimic octopus, can adjust its color according to the environment for protective camouflage. , Inspired by this, stimuli-responsive photonic materials have attracted extensive attention for their potential in the development of applications due to their various functionalities and adjustability. Examples of potential applications are sensing, decoration, and anti-counterfeit devices. , The materials are able to reversibly adjust their color in response to external stimuli, including temperature, humidity, , light, electricity, , magnetism, and stress. , In particular, thermochromic photonic materials that can adjust their reflection band automatically in response to ambient temperature are energy-saving and user-friendly …”
Section: Introductionmentioning
confidence: 99%
“…Similar RPPs in response to water or other stimulus can also be printed on cholesteric liquid crystals. [ 77–89 ] For example, Schenning's group [ 83,84 ] demonstrated that RPPs can be prepared by selective cross‐linking the cholesteric photonic film, which show reversible color under solvent or different temperature. Despite these successes, most of the fabricated RPPs show simple change in color contrast in response to the solvents.…”
Section: Introductionmentioning
confidence: 99%